Experiences and impacts of psychological support following adverse neonatal experiences or perinatal loss: a qualitative analysis - Gill Thomson; Lara McNally; Rebecca Nowland (BMC, 2024)
Abstract Background Poor parental mental health in the perinatal period has detrimental impacts on the lives and relationships of parents and their babies. Parents whose babies are born premature and/or sick and require neonatal care or those who experience perinatal loss are at increased risk of adverse mental health outcomes. In 2021 a North-West charity received funding to offer psychological support to service users of infants admitted to neonatal care or those who had experienced perinatal loss, named the Family Well-being Service (FWS). The FWS offered three different types of support - ad hoc support at the neonatal units or specialist clinics; one-to-one person-centred therapy; or group counselling. Here we report the qualitative findings from an independent evaluation of the FWS. Methods Thirty-seven interviews took place online or over the phone with 16 service users (of whom two took part in a follow-up interview), eight FWS providers and 11 healthcare professionals. Interviews were coded and analysed using thematic analysis. Results The analysis revealed two themes. 'Creating time and space for support' detailed the informational, contextual, and relational basis of the service. This theme describes the importance of tailoring communications and having a flexible and proactive approach to service user engagement. Service users valued being listened to without judgement and having the space to discuss their own needs with a therapist who was independent of healthcare. Communication, access, and service delivery barriers are also highlighted. The second theme - 'making a difference' - describes the cognitive, emotional, and interpersonal benefits for service users. These included service users being provided with tools for positive coping, and how the support had led to enhanced well-being, improved relationships, and confidence in returning to work. Conclusion The findings complement and extend the existing literature by offering new insights into therapeutic support for service users experiencing adverse neonatal experiences or perinatal loss. Key mechanisms of effective support, irrespective of whether it is provided on a one-to-one or group basis were identified. These mechanisms include clear information, flexibility (in access or delivery), being independent of statutory provision, focused on individual needs, active listening, the use of therapeutic tools, and positive relationships with the therapist. Further opportunities to engage with those less willing to take up mental health support should be developed.